Progress in Entrepreneurship Education and Training New Methods, Tools, and Lessons Learned from Practice - Block, Joern H.; Halberstadt, Jantje; Högsdal, Nils; Kuckertz, Andreas; Neergaard, Helle (FGF Studies in Small Business and Entrepreneurship, 2023)
The education of future entrepreneurs shapes how we will live in the future, and proper entrepreneurship education is thus of utmost importance. Entrepreneurship educators and researchers constantly renew tools, interventions, and training programs for entrepreneurship education and adapt them to the specific needs of entrepreneurs and developments in the entrepreneurship ecosystem. This open-access book is based on this background and offers expert insights that highlight context-specificity and discuss training methods and tools that are impact-oriented. The authors represent multiple institutional and cultural backgrounds, to provide a useful resource with new ideas for the community of entrepreneurship educators, facilitators, and scholars. Based on the chapters, the editors of the volume also offer several propositions and critical insights important for the current state of entrepreneurship education and its future development. This book will be a valuable resource for entrepreneurship educators and education policymakers alike.